Presidential Threshold Polemic in the 2019 Election and Before the 2024 Election Contest in Indonesia - Ahmad Shirotol; Mhd. Erwin Munthe; Ridwan Harahap; Alfi Hasanah (Magister Ilmu Hukum Fakultas Hukum Universitas Riau, 2023)
The application of the presidential threshold in the presidential nomination election in Indonesia gave rise to various controversies and became a topic of discussion in the country's political system. This research wants to see the presidential threshold polemic in the 2019 election and before the 2024 election contestation in Indonesia. The type of research used is normative legal research. The findings in the 2019 election of the presidential threshold polemic that occurred were a number of political parties objecting to a high threshold, restrictions on the freedom of the people/the best sons and daughters who wanted to advance in the presidential election, the public were given choices that were not varied, weakened the presidential system and contradicted the 1945 Constitution Then the polemic leading up to the 2024 election, namely: elite candidates dominating, alternative candidates are limited, consideration of the Constitutional Court is problematic, article 222 of the law is contrary to article 6A (2) of the 1945 Constitution and democratic space is now limited.